Preliminary codesign and testing of a feedback tool to improve the quality of peer appraiser documentation for medical revalidation. Issue 1 (2nd January 2019) - Murie, Jill; MacWalter, Gordon; Bowie, Paul
ABSTRACT: Medical appraisal and associated revalidation are mandatory for doctors in the United Kingdom. However, the quality of appraisal documentation, which informs the revalidation process on a doctor's fitness-to-practise, is known to be variable. This preliminary study aimed to develop and test a formative educational tool that could be used, as part of routine appraiser training in the general practice setting, to review and provide evidence and feedback on the quality of documentation completion. A mixed-methods study was undertaken based on codesign principles, which elicited the views and opinions of medical appraisers, appraisal leads and medical managers on the content of an educational tool designed to reduce variation in appraisal paperwork completion. The study team created a 24-item educational tool covering six domains of the appraisal process. Domains included 'reflection on practice', 'knowledge, skills and performance' and 'quality and safety'. The tool was piloted amongst appraisers and received positive feedback. This study contributes practical knowledge to help reduce variation in appraisal documentation. The tool can be used to streamline the completion of appraisal documentation by appraisers. It may provide a level of quality assurance and contribute to providing fair, objective and measurable grounds for revalidation.